Mahishasuramardini (Temple 6) of the Baroli Group of Temples - Temples of India Project Team (Jio Institute, 2024)
Temple 6 is dedicated to Mahishasuramardini. The temple is situated next to the Vamana Temple and to the right side of the Ghateshwar Temple. It is one of the well-preserved temples and biggest temples in the complex, with all its parts intact. The temple is east-facing and consists of a mukhamandapa (front porch), antarala (vestibule), and a garbhagriha (sanctum sanctorum).